2009
DOI: 10.1016/j.jbi.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Automatically extracting cancer disease characteristics from pathology reports into a Disease Knowledge Representation Model

Abstract: We introduce an extensible and modifiable knowledge representation model to represent cancer disease characteristics in a comparable and consistent fashion. We describe a system, MedTAS/P which automatically instantiates the knowledge representation model from free-text pathology reports. MedTAS/P is based on an open-source framework and its components use natural language processing principles, machine learning and rules to discover and populate elements of the model. To validate the model and measure the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 12 publications
2
111
0
Order By: Relevance
“…We found that over 90% recall and precision are achievable in the extraction of staging term-value(s) data, even when pathologists use several different ways of representing them. This compares very well with even much more complex techniques [17,18]. In the case studied, the completeness of cancer staging was increased by up to a third.…”
Section: Discussionsupporting
confidence: 67%
“…We found that over 90% recall and precision are achievable in the extraction of staging term-value(s) data, even when pathologists use several different ways of representing them. This compares very well with even much more complex techniques [17,18]. In the case studied, the completeness of cancer staging was increased by up to a third.…”
Section: Discussionsupporting
confidence: 67%
“…Rule based systems and machine learning systems are both used, and in some cases in combination. Coden et al (2009) built a model called Cancer Disease Knowledge Representation Model, which has nine classes including anatomical site, histology, and metastatic tumor. Evaluation found that recall was between 76% and 100% and precision was between 72% and 100% for all classes except metastatic tumor where both precision and recall were lower.…”
Section: Related Researchmentioning
confidence: 99%
“…For a review of the research area, see Spasić et al (2014). Coden et al (2009) extracted information from pathology reports for colon cancer. A combination of rules and machine learning were used to extract nine different classes from the reports.…”
Section: Previous Researchmentioning
confidence: 99%